2014
DOI: 10.1590/1516-635x160237-42
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different vitamin D sources and calcium levels in the diet of layers in the second laying cycle

Abstract: This study evaluated the effects of different sources of vitamin D and calcium levels on performance, egg quality and bone strength of hens in the second production cycle. A total of 384 Hy-Line W36 birds with 80 weeks of age were used, alloted into 3 x 4 factorial design (sources of vitamin D: cholecalciferol; 25(OH)D 3 and 1.25(OH) 2 D 3 x calcium levels: 2.85, 3.65; 4.45 and 5.25%) with four replicates and eight birds each. The performance was evaluated for three cycles of 28 days each, egg quality was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 18 publications
8
16
0
Order By: Relevance
“…In contrast, the level of Ca did not affect the EW. Nonetheless, the source of VD 3 influenced ( P < 0.05) LR, FCR, and EW, showing improved results of laying hens with 25-(OH)D 3 and cholecalciferol ( 40 ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, the level of Ca did not affect the EW. Nonetheless, the source of VD 3 influenced ( P < 0.05) LR, FCR, and EW, showing improved results of laying hens with 25-(OH)D 3 and cholecalciferol ( 40 ).…”
Section: Resultsmentioning
confidence: 98%
“…These may differ due to the role of Ca in regulating the reproductive hormones and ovary growth ( 5 ). Nascimento et al ( 40 ) found that there was no interaction between the different sources of vitamin D at a 2,000-IU/kg diet from VD 3 , 25-(OH)D 3 , 1,25-(OH) 2 D 3 , and four calcium levels from 2.85 to 5.25%, with intervals of 0.80% in all egg production traits. However, a significant quadratic component of the contrast analysis for the level of calcium in LR and FCR was observed, showing better productive characteristics at 4.12 and 4.09% Ca, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, lots of efforts are being employed to improve the productive performance of aged laying hens using nutritional interventions, including but not restricted to the supplementation of the diet with the exogenous enzymes, prebiotics and probiotics, minerals (calcium and zinc, etc. ), and vitamins such as vitamin D ( VD ) and biotin ( Abdelqader et al., 2013 , Kim et al., 2013 , Nascimento et al., 2014 , Ghasemian and Jahanian, 2016 , Tsai et al., 2016 ). Owing to their beneficial effects on reproduction, antioxidant activity and other physiological mechanisms ( Combs Jr. and McClung, 2016 ), vitamins have justifiably attracted a lot of interest in the laying hen industry.…”
Section: Introductionmentioning
confidence: 99%
“…However, the advancing aging of laying hens is invariably accompanied by the reduced ability of VC synthesis and VD metabolism in the kidneys ( Abe et al., 1982 , Gan et al., 2018 ) and the attenuated absorption of vitamin B complex in the intestine ( Pannerec et al., 2018 ). Some previous studies demonstrated that supplementation with a high concentration of VD/K in the diet of old laying hens enhanced the laying rate and the concentration of VD/K in the eggs ( Park et al., 2005 , Nascimento et al., 2014 ). Similarly, a higher inclusion rate of VC in 80-wk-old laying hens also improved antioxidant ability and immunity ( Gan et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The specific gravity achieved was probably due to the relatively similar calcium and phosphorus content of the dietary treatment (Table 1), so the calcium content in the eggshell was also no different. According to Nascimento et al (2014), egg specific gravity was influenced significantly by calcium consumption. This statement is supported by the opinion of Harmayanda et al (2016) which stated that calcium consumption has a positive effect on egg specific gravity.…”
Section: Egg Specific Gravitymentioning
confidence: 99%